1987
DOI: 10.1128/jb.169.10.4668-4673.1987
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of amino acid transport in the facultatively heterotrophic cyanobacterium Synechocystis sp. strain 6803

Abstract: The existence of active transport systems (permeases) operating on amino acids in the photoautotrophic cyanobacterium Synechocystis sp. strain 6803 was demonstrated by following the initial rates of uptake with 14C-labeled amino acids, measuring the intracellular pools of amino acids, and isolating mutants resistant to toxic amino acids. One class of mutants (Pfa1) corresponds to a regulatory defect in the biosynthesis of the aromatic amino acids, but two other classes (Can1 and Aza1) are defective in amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 22 publications
5
57
2
Order By: Relevance
“…Glutamine uptake in strains CSMJ7 and CSMJ8 was most severely affected at 100 µM (∼5% of the wild-type levels) than at 1 µM (∼40%). These results are consistent with previously reported data (Labarre et al 1987;Flores and Muro-Pastor 1990) and suggest that Bgt, which is a high-affinity system for basic amino acids, represents a low-affinity, high-capacity system for glutamine. Uptake of histidine in the bgt mutants was also more severely affected at 100 µM (∼4% of the wild-type levels) than at 1 µM (∼25%).…”
Section: Basic Amino Acid and Glutamine Permeasesupporting
confidence: 83%
See 3 more Smart Citations
“…Glutamine uptake in strains CSMJ7 and CSMJ8 was most severely affected at 100 µM (∼5% of the wild-type levels) than at 1 µM (∼40%). These results are consistent with previously reported data (Labarre et al 1987;Flores and Muro-Pastor 1990) and suggest that Bgt, which is a high-affinity system for basic amino acids, represents a low-affinity, high-capacity system for glutamine. Uptake of histidine in the bgt mutants was also more severely affected at 100 µM (∼4% of the wild-type levels) than at 1 µM (∼25%).…”
Section: Basic Amino Acid and Glutamine Permeasesupporting
confidence: 83%
“…Nat is a transport system for neutral amino acids and histidine that seems to be widespread in cyanobacteria (Montesinos et al 1997). In contrast with earlier suggestions (Labarre et al 1987), our results show that Nat also transports glutamine and that it does so with high affinity (K s , 2 µM). Thus, the high-affinity glutamine transport system described by Labarre et al (1987) is Nat itself.…”
Section: Synechocystis Amino Acid Permeasescontrasting
confidence: 56%
See 2 more Smart Citations
“…PCC 6803 is unique because it exhibits high glutamate uptake activity. 20,21) Quintero et al (2001) 9) found that SygltS (slr1145) and Sygtr (sll1102-4) are involved in glutamate uptake in Synechocystis sp. PCC 6803, but the double mutants of these genes reduced uptake activity only to 40-55% of the wild-type values, suggesting the presence of an additional glutamate uptake system.…”
Section: Discussionmentioning
confidence: 99%